Study and protection of radon springs in the neighbor of Tomsk - Natalya Mikhailovna Semenova; Aleksandr Dmitrievich Nazarov; Natalya Gennadievna Sidorina; Platon Alekseevich Tishin (Известия Томского политехнического университета: Инжиниринг георесурсов, 2016)
Up to the present time the composition and quality of water in spring wells near Tomsk are not fully investigated. Hydrochemical and balneological properties of waters were virtually neglected. Specific activity of radon-222 in spring wells of Tomsk is 2-25 Bq/dm3. The highest levels of radon occurrence are discovered in subsurface waters of the south-east territory of Tomsk in the basin of the Ushaika river. Radon spring wells were historical source of water supply. In the suburban areas, where these springs are located, they are still used and protected by the local population as a source of clean water. Due to the intensive development of suburban areas, the radon springs and their natural surroundings are of key importance for determining ecological nets and areas requiring special protection. Radon spring wells are integral to the natural heritage of Tomsk region and they are subject to protection in relation to their location, water composition and quality. The main aim of study is to analyze the traditions and priorities of study and use of radon springs of Tomsk region; full geoecological assessment of the most eligible radon locations outside of Tomsk in terms of ensuring their special protection. The methods used in the study: study of literature and normative and legal sources that determine current status of radon springs as natural resource of traditional use and nature protection; mapping radon springs locations in the valley of the Ushayka River; testing springs; physical and chemical, also radiological study of spring waters. The results. The paper introduces the results of a comparative analysis of water samples from popular spring wells of Tomsk. The authors have studied in details the spring «Chistiy Kluch» (222Rn=39,5 Bq/dm3) on the right bank of the Ushaika river near Zavarzino village. The analysis of water and surrounding territory showed that the spring is the valuable natural site requiring a status of specially protected territory of regional significance.